Upaya Penurunan Suhu Tubuh Dengan Kompres Hangat Pada Anak DBD Di RSPA Boyolali - Susilo, Ahmad Syarif Aziz, Irdawati, S.Kep., Ns., M.Si. Med (2016)
Background: Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue viruses (arboviruses) that enter the body through the bite of aedes aegepti, the symptoms are high fever, headache and back of the eye. Until now the disease Dengue Hemorrhagic Fever (DHF) is still a serious problem in Central Java Province, the death toll due to Dengue Hemorrhagic Fever (DHF) is increasing, not only in the case of children, but also teenagers and even adults. Patients with Dengue Hemorrhagic Fever (DHF) will experience high heat is very dangerous if not promptly scaled back can cause seizures, to anticipate the occurrence of seizures effort that must be done is to lower the body temperature, there is acting alone can be done by a nurse to help lower the body temperature, by way of warm compresses, and meet the fluid needs of children, because, compress with warm water will dilate blood vessels and blood flow increases smoothly so that the heat in the body more quickly discharged into the air, and meet the needs of fluid in children may replace fluids lost through fluid in the body will evaporate during an increase in body temperature. Purpose: Efforts to lower body temperature in children with Dengue Hemorrhagic Fever (DHF) is by way of a warm compress. Methods: Study of cases, the authors attempt to take action to lower the body temperature by using warm compresses in children with Dengue Hemorrhagic Fever (DHF), the first steps were used that assessment, data analysis, intervention, implementation, and evaluation of nursing. Results: After done actions warm compresses for 20 minutes, the patient's temperature was down 0.2 OC, body temperature before doing a warm compress is 37.3 OC after doing a warm compress body temperature dropped to 37.1 OC. Actions undertaken warm compresses to the patient is considered effective because the patient's body temperature can drop 0.2 OC after warm compresses for 20 minutes.